The Underrepresentation of Knowledge Production in Latin American Social Sciences - Guzmán-Valenzuela, Carolina (International Higher Education, 2025)
<h3 id="although-latin-american-social-sciences-have-expanded-significantly-in-recent-decades-they-remain-structurally-marginal-within-the-global-academic-system-this-article-analyzes-the-persistence-of-epistemic-hierarchies-that-limit-the-visibility-and-impact-of-social-science-research-produced-in-latin-america-it-argues-that-current-global-knowledge-structures-continue-to-prioritize-english-language-stem-outputs-from-wealthy-institutions-in-the-global-north-thereby-marginalizing-local-languages-regional-collaborations-and-context-sensitive-research" data-pm-slice="1 1 []">Although Latin American social sciences have expanded significantly in recent decades, they remain structurally marginal within the global academic system. This article analyzes the persistence of epistemic hierarchies that limit the visibility and impact of social science research produced in Latin America. It argues that current global knowledge structures continue to prioritize English-language STEM outputs from wealthy institutions in the Global North, thereby marginalizing local languages, regional collaborations, and context-sensitive research.